Evaluation of 3-Borono-l-Phenylalanine as a Water-Soluble Boron Neutron Capture Therapy Agent - Naoya Kondo; Fuko Hirano; Takashi Temma (MDPI AG, 2022)
Although 4-borono-l-phenylalanine (4-BPA) is currently the only marketed agent available for boron neutron capture therapy (BNCT), its low water solubility raises concerns. In this study, we synthesized 3-borono-l-phenylalanine (3-BPA), a positional isomer of 4-BPA, with improved water solubility. We further evaluated its physicochemical properties, tumor accumulation, and biodistribution. The water solubility of 3-BPA was 125 g/L, which is more than 100 times higher than that of 4-BPA. Due to the high water solubility, we prepared the administration solution of 3-BPA without a solubilizer sugar, which is inevitably added to 4-BPA preparation and has adverse effects. In in vitro and in vivo experiments, boron accumulation in cancers after administration was statistically equivalent in both sugar-complexed 3-BPA and 4-BPA. Furthermore, the biodistribution of 3-BPA was comparable with that of sugar-complexed 3-BPA. Since 3-BPA has high water solubility and tumor targetability equivalent to 4-BPA, 3-BPA can replace 4-BPA in future BNCT.